2012
DOI: 10.1016/j.jns.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and outcome of a web-based self-help intervention for depressive symptoms in patients with multiple sclerosis: A pilot study

Abstract: This study suggests that applied web-based PST is feasible and reduces depressive symptoms in MS patients. Especially MS patients who experience disease-related or other barriers to participate in face-to-face counselling could benefit. However, ways to increase compliance should be considered. A randomized controlled trial is recommended to more extensively investigate effectiveness of this intervention in treating depressive symptoms in MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 42 publications
1
40
1
Order By: Relevance
“…30 Our results are also in line with randomised trials done in otherwise healthy patients with depression and without comorbid somatic disorders, which lends support to the usefulness of iCBT in general 31 and speci cally the Deprexis programme in patients with major depressive disorder. 18,32,33 Few randomised trials have assessed the e ects of pharmacological or behavioural interventions to treat depression in patients with multiple sclerosis.…”
Section: Discussionsupporting
confidence: 86%
“…30 Our results are also in line with randomised trials done in otherwise healthy patients with depression and without comorbid somatic disorders, which lends support to the usefulness of iCBT in general 31 and speci cally the Deprexis programme in patients with major depressive disorder. 18,32,33 Few randomised trials have assessed the e ects of pharmacological or behavioural interventions to treat depression in patients with multiple sclerosis.…”
Section: Discussionsupporting
confidence: 86%
“…Boeschoten et al looked into the feasibility of web-based self help intervention for MS patients with depression [60]. In their cohort they found significantly decreased levels of depression as measured by the Beck Depression Inventory.…”
Section: Depression and Fatiguementioning
confidence: 99%
“…As a consequence, evidence will be lacking whether the intervention could be effective for this group of patients. However, our pilot-study [29] showed that patient with more severe depressive symptoms experienced more benefit from the intervention than patients with fewer depressive complaints. Moreover, patients with fewer depressive symptoms at baseline (<20) were more likely to drop out of treatment and indicated to be less satisfied with the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative data from this research group showed that existing Internet-based CBT packages might not just be appropriate for MS patients due to MS related physical and cognitive impairments, inappropriate content, social isolation and problems with computer use [27]. However, data from our recent pilot study on Internet-based treatment for depression in MS showed evidence that Internet-based self-help PST treatment [28], adjusted to MS patients, can be a feasible treatment [29]. Patients reported satisfaction with the intervention which reduced depressive symptoms, especially in those MS patients who completed the intervention.…”
Section: Introductionmentioning
confidence: 99%